Validation of UV Spectrophotometry Method for Determination of Lopinavir and Ritonavir Simultaneously - Siti Umi Anisah; Asri Darmawati; Amirudin Prawita (Berkala Ilmiah Kimia Farmasi, 2021)
Lopinavir and ritonavir are anti-viral compounds that have similar chemical structures and overlapping UV spectral profiles. The combination of these two compounds is being promoted as an anti-COVID19 drug. Determination of these two compounds simultaneously using UV spectrophotometry method requires special technique so that the result will be valid. The purpose of this study was to obtain a suitable analytical technique using UV spectrophotometry for the determination of lopinavir-ritonavir simultaneously that fulfill the method validation requirement. In this study, the simultaneous equation technique, absorptivity comparison factor, and first derivative technique were used to overcome the effect of lopinavir/ritonavir absorbance at selected wavelengths for determination of each compound simultaneously. The one-way ANOVA statistical test was used to compare the result of the three analytical techniques. The results showed that the three techniques fullfilled the AOAC requirements for selectivity and linearity. The accuracy and precision test result have not met the requirements of the AOAC method validation. Statistically. the one-way ANOVA analysis showed there was a significant difference between the mean recovery of lopinavir using the absorptivity factor and first derivative technique. Whereas, there was no significant differences among the mean of ritonavir recoveries that were determined using those three techniques. As conclusion, that the UV spectrophotometric method using the simultaneous equation technique, the absorptivity factor technique, and the derivative technique for assaying the lopinavir and ritonavir simultaneously met the requirements for selectivity and linearity parameters. However, the accuracy and precision have not met the requirements. The first derivative technique is suitable for further developed for ritonavir and lopinavir determination simultaneously